Exploring dihydropyrimidone derivatives as modulators of carbohydrate catabolic enzyme to mitigate diabetes - Syed Parween Ali; Farheen Mansoor; Shaymaa Fadhel Abbas Albaayit; Farman Ali; Ayed A. Dera; Muhammad Shahbaz; Jawad Ullah; Hailah M. Almohaimeed; Reem M. Gahtani; Ahmed M. Abdulfattah; Fahad M. Alshabrmi; Sarfaraz Alam; et al. (Scientific Reports)
Abstract Diabetes is a prevalent and serious metabolic disorder affecting millions globally, and it poses extensive health risks due to elevated blood glucose levels. One promising approach for managing diabetes is the inhibition of α-glucosidase, an enzyme that plays a crucial role in carbohydrate metabolism. Targeting α-glucosidase can help delay glucose absorption, thus controlling postprandial blood sugar spikes. Dihydropyrimidones, a core structural class present in various biologically active natural compounds, have been recognized for their diverse therapeutic potential, including anti-diabetic properties. In this study, we evaluated a library of previously synthesized 37 Dihydropyrimidone derivatives to assess their potential as α-glucosidase inhibitors. We identified 34 derivatives with significant inhibitory activity, exhibiting IC50 values in the range of 5.30–56.72 µM. Among these, compounds 2, 4–7, 9–11, 13–16, 31, 32, and 33 demonstrated high potency, with IC50 values below 20 µM; the most active compound, 5, achieved an IC50 of 5.30 µM. A detailed kinetic study on compound 5 revealed a competitive inhibition mode with a Ki value of 16.10 ± 0.0075 µM. Additionally, cytotoxicity assays confirmed that compound 5 is non-toxic to BJ cell lines, underscoring its safety for therapeutic use. The computational studies further supported the inhibitory potential by illustrating key interactions and binding affinities between the Dihydropyrimidone derivatives and the α-glucosidase, highlighting these compounds as promising candidates for diabetes management.